Young Hegelians and Karl Marx - "Mclellan, David" (London, 1980)
The premis of this study is that Marx's world view was very much a product of its time, and as such, it can only be understood in relation to the intellectual climate in which it was conceived. In this text, the author examines the influential force of the Young Hegelian movement, and discusses the work of the leading Young Hegelians, including Bruno Bauer, Feuerbach, Stirner and Hess - and their influence on Marx.
Keywords: "Philosophy, German-19th Century."